La marcha nacional #14N: la muerte de Inti y Brayan por causa de la represión policial - Torres Montero, Luis Francisco (2021)
The professional sufficiency report that I send with the purpose of graduating of Communication Bachelor¿s from the University of Lima, it is about the daily journalistic coverage that I made for the newspaper Diario Uno, with the topic “The March of 14-N: the young people who lost their lives because the Police ”, during the year 2020. I try to explain the production of informative notes that I wrote in my opinion column Malas Palabras, before and after the events, with the purpose of being the most objective, neutral, and critical as possible. For this reason, I present the principal journalistic articles produced during the period of November 14 - November 27, 2020, on the other hand I will describe the most important lessons learned from this coverage as a communication professional.